2017
DOI: 10.29312/remexca.v8i5.113
|View full text |Cite
|
Sign up to set email alerts
|

Características de la cubierta de un túnel efecto en radiación, clorofila y rendimiento de calabacita

Abstract: Debido que la agricultura bajo cubiertas plásticas es una alternativa para mejorar la producción de cultivos hortícolas, el objetivo de este estudio fue evaluar el efecto de cuatro tipos de cubiertas de túneles de diferentes materiales y colores en la transmitancia de la radiación y su relación con contenido de clorofila, crecimiento y rendimiento de un cultivo de calabacita (Cucurbita pepo) cv. Zucchini. El estudio se realizó durante el ciclo de producción otoño-invierno 2015 a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…A similar PAR behavior to that observed during the day of our trial was found by Del Ángel-Hernández et al [5] in Nuevo León (Mexico). The differences in the PAR transmittance between the pilot greenhouses (Tables 10 and 11) and those obtained by a spectroradiometer in the laboratory (Table 1) may be due to the degradation and accumulation of dust on the covers and the deck angle [62], since when the analyses of the optical properties were performed with the spectroradiometer, the samples were cleaned before the analysis, while once placed in the greenhouses for field evaluation, they were fully exposed to degradation and dirt.…”
Section: Evaluation Of Environmental Factors In the Fieldsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar PAR behavior to that observed during the day of our trial was found by Del Ángel-Hernández et al [5] in Nuevo León (Mexico). The differences in the PAR transmittance between the pilot greenhouses (Tables 10 and 11) and those obtained by a spectroradiometer in the laboratory (Table 1) may be due to the degradation and accumulation of dust on the covers and the deck angle [62], since when the analyses of the optical properties were performed with the spectroradiometer, the samples were cleaned before the analysis, while once placed in the greenhouses for field evaluation, they were fully exposed to degradation and dirt.…”
Section: Evaluation Of Environmental Factors In the Fieldsupporting
confidence: 91%
“…Related to the radiometric properties, the behavior of the absorbance was inversely proportional to the transmittance and reflectance [5]. The behavior of the transmittance of the blue EPC was similar to that described by Larsen et al [39].…”
Section: Radiometric Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…Trabajos como los de Del Ángel-Hernández et al (2017) en una investigación en calabacita (Cucurbita pepo cv. Zucchini), reportaron que plantas que crecieron bajo un túnel con policarbonato de color claro (el de mayor transmitancia 82,57%), tuvieron mayor contenido de clorofila y mayor desarrollo foliar.…”
Section: Fuente: Autoresunclassified